De la “Taverne du Chat Dansant” à l’“Underground”: l’importance du bar comme espace de socialisation dans les romans de Marie-Claire Blais - Pich-Ponce, Eva (Ponti/Ponts, 2021)
This study aims to analyse the significance of bars in Un Joualonais sa Joualonie (1973) and Les nuits de l’Underground (1978), by Quebec author Marie-Claire Blais. Blais is one of the most important writers of contemporary Quebec literature. In her works, the bars of Montreal become privileged spaces where one can find a freedom which does not exist anywhere else. In these places new sociabilities are constructed and they reflect the social changes that characterized the Quebec of the 70s. This analysis will show how bars are used in these novels as spaces which highlight social relationships and social claims. Through these places, the narratives suggest the possibilities of communication and the threats of the lack of tolerance. In Blais’ novels, bars allow the author to stress the importance of a new social order based on acceptance and compassion.